Theoretical investigation on monomer and dimers of Inhibitor of cytochrome P450 enzymes: 1-aminobenzotriazole - Manzur, Maria Eugenia (2023)
In this research, structures and properties of monomer and two dimers (1 and 2) of inhibitor of cytochrome P450 enzymes, 1-Aminobenzotriazole (ABT) have been studied by using functional hybrid B3LYP/6-311++G** calculations. The very good correlations observed between theoretical and experimental 1H-, 13C-NMR, FT-IR and FT-Raman spectra suggest that C-H···N interactions of dimeric species should be expected in the solid phase, as was observed in the experimental crystalline structure of a quinolin benzotriazole derivative. NBO and AIM calculations suggest that dimer 2 with inverted positions of its monomers could be present in the solid phase because it evidence higher stabilities in both media. On the other hand, frontier orbitals studies support a higher reactivity of dimer 2 of ABT higher than the monomer and dimer 1, for which, the presence of dimer 2 containing N-NH2 groups in ABT could justify the biological activities observed for this species with gap values between 4.5933 and 4.8164 eV different from antiviral agents containing the C-NH2 moiety, as amantadine and chloroquine whose gap values are around 4.3012-4.1116 eV. Finally, the presence of bands of monomer and of both dimers are predicted in the vibrational spectra and, hence, its completes assignments have been performed. The scaled force constants for the three studied species are also reported.